Human body parts detection using YCbCr color space - Johan, Nurul Fatiha; Mohd Mustafah, Yasir; Alang Md Rashid, Nahrul Khair (Trans Tech Publications Ltd., Switzerland, 2013)
Skin color is proved to be very useful technique for human body parts detection. The detection of human body parts using skin color has gained so much attention by many researchers in various applications especially in person tracking, search and rescue. In this paper, we propose a method for detecting human body parts using YCbCr color spaces in color images. The image captured in RGB format will be transformed into YCbCr color space. This color model will be converted to binary image by using color thresholding which contains the candidate human body parts like face and hands. The detection algorithm uses skin color segmentation and morphological operation.